Plum Island - DeMille, Nelson (New York Warner Books, 1997)
Taking the best elements from two of his most outstanding bestsellers, The Gold Coast and The General's Daughter, Nelson DeMille combines the breathless suspense of an expertly wrought murder mystery with his wry perspective on a peculiarly American social scene to deliver an enthralling and compelling story. Wounded in the line of duty, NYPD homicide detective John Corey convalesces in the Long Island township of Southold, home to farmers, fishermen -- and at least one killer. Tom and Judy Gordon, a young, attractive couple Corey knows, have been found on their patio, each with a bullet in the head. The local police chief, Sylvester Maxwell, wants Corey's big-city expertise, but Maxwell gets more than he bargained for. The early signs point to a burglary gone wrong.
Keywords: New York (State)--Plum Island -- Treasure troves -- Police